BERMAIN “EGO” PSIKOANALITIS DALAM BIMBINGAN DAN KONSELING PADA ANAK TUNA GRAHITA - Ahmad Syamsul Muarif (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
The aim of this research is to find out how to provide guidance and counseling techniques for mentally retarded children, then find out what the process of educating mentally retarded children is. Children with mental retardation or also known as mentally retarded because of their limited intelligence make it difficult for them to take part in classical educational programs in regular schools, therefore mentally retarded children need special educational services that are tailored to the child's abilities. The method used is a qualitative case study, with data analysis techniques used, namely pattern matching and explanation creation. The results of this research show that children with special needs can be minimized, but in a small way and over a very long period of time. For example, how to communicate, a counselor must be able to provide guidance services for this kind of thing. The causes of mental retardation in children are, firstly, it could be heredity factors, parenting style factors, nutritional factors, social factors, and so on. Because it is possible that when the baby is in the womb he lacks vitamins, this could also be a cause of mental retardation in children. The hope is that with psychoanalytic play therapy, mentally disabled children will receive guidance and learning to increase their IQ. Of course, this kind of thing is done by providing lessons and examples of games repeatedly in play therapy. So by giving examples over and over again, they can easily memorize what their teacher has taught them even though they are slow to digest it.